1997
DOI: 10.1111/j.1600-0560.1997.tb01584.x
|View full text |Cite
|
Sign up to set email alerts
|

Mode of c‐myc protein expression in Spitz nevi, common melanocytic nevi and malignant melanomas

Abstract: The expression of c-myc protein was studied in formalin-fixed, paraffin-embedded sections of 16 compound Spitz nevi (SNs), 20 ordinary compound melanocytic nevi (MNs) and 30 malignant melanomas (MMs), using monoclonal antibody 9E10 and an immunoperoxidase technique. Nine (56%) SNs, 16 (80%) MNs and 23 (77%) MMs showed positive reactions in some of the tumor cells (P = non-significant). The staining reactions were mostly cytoplasmic, and moderate to strong in intensity. The frequencies of positively stained cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
1
10
1
Order By: Relevance
“…Our results both on RNA and protein level confirm published data showing similar cmyc expression on the protein level in primary melanoma and in nevi (Bergman et al, 1997) and a higher expression in melanoma metastases (Grover et al, 1996). Regarding the relation of c-myc expression to the number of c-myc FISH signals, nevi and a subset of primary tumours with a tumour thickness up to 1.04 mm have both a combination of low expression and low signal number, whereas primary melanomas with a high tumour thickness (5.2 mm; 11.0 mm; 12.1 mm) have either an elevated expression or a higher number of signals (Table 2, Figure 5).…”
Section: Discussionsupporting
confidence: 92%
“…Our results both on RNA and protein level confirm published data showing similar cmyc expression on the protein level in primary melanoma and in nevi (Bergman et al, 1997) and a higher expression in melanoma metastases (Grover et al, 1996). Regarding the relation of c-myc expression to the number of c-myc FISH signals, nevi and a subset of primary tumours with a tumour thickness up to 1.04 mm have both a combination of low expression and low signal number, whereas primary melanomas with a high tumour thickness (5.2 mm; 11.0 mm; 12.1 mm) have either an elevated expression or a higher number of signals (Table 2, Figure 5).…”
Section: Discussionsupporting
confidence: 92%
“…Given these data and the fact that human benign nevi contain senescent melanocytes (3, 12, 13), we were surprised by previous reports suggesting that human nevi express proliferation-promoting Wnt targets, such as cyclin D1, c-myc, and MITF (40)(41)(42). However, we confirmed that many melanocytic nests of human benign nevi exhibited coincident expression of nuclear β-catenin and its proliferation-promoting targets, cyclin D1 and c-myc (Fig.…”
Section: Resultscontrasting
confidence: 44%
“…Thus, neither HMB-45, AgNOR, cyclin D1, c-myc, c-fos, telomerase, cdc-7, anti-leptin receptor, BCL-2, p53 nor p16 proved helpfulness in distinguishing Spitz nevi from melanoma. 13,[24][25][26][27][28][29][30][31][32][33] In this study, we performed a comparative analysis of protein expression using a wide panel of antibodies between classical Spitz nevi and vertical growth phase melanomas. Using tissue microarray analysis, a high-throughput means that allows the evaluation of several markers in a large number of melanocytic tumors, we identified a specific protein expression profile differentiating between typical Spitz nevus and non-spitzoid melanoma (Table 2).…”
Section: Discussionmentioning
confidence: 99%